Interaction Between the Cage Floor and the Variation of Different Fur Colors the Behavior and Against Perfomans of Kampung Super Chickens (Gallus domesticus Sp) - J. Kurniawan; E. Tugiyanti; Rosidi (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
The Super Kampung chicken has a non-uniform coat color, this is related to the genetics of its parents. Genetics has a relationship with aggressiveness and this must be supported by a supportive cage floor. This study aims to examine the effect of the interaction between variations in coat color and different types of cage floors. The experimental material used was 120 DOC which were maintained for 70 days. This study used a completely randomized design (CRD) with a 5x2 factorial pattern with 10 treatments, namely 5 coat colors (W) and 2 cage floors (L), the treatments were repeated 3 times so there were 40 experimental units. The results showed that there was an interaction between the color of the coat and the type of floor of the cage on the pecking order variable. Color variation had a very significant (P<0.01) effect on roaming behavior, but had no significant effect (P>0.05) on pecking order behavior, feed conversion and performance index. The cage floor treatment had no significant effect (P>0.05) on all variables. The conclusion of this research is genetic such as genes (SORCS2) will be related to the level of aggressiveness. So that there are interactions of these two factors to the intensity behavior of pecking and pecking orders.